To Explore the Effects of Acupuncture and Medical Treatment at Different Times on the Gastrointestinal Reaction and White Blood Cell Count of Patients with Lung Cancer Chemotherapy - Qingchun Zhao; Hui Du; Jinghao Liu; Yu Hua; Xiaoyu Niu; Jun Chen (Applied Bionics and Biomechanics)
Objective. To explore and analyze the effects of acupuncture and medical treatment at different times on the gastrointestinal reaction and leukocyte count of patients with lung cancer undergoing chemotherapy. Methods. Select 224 lung cancer chemotherapy patients admitted to our hospital and randomly divide them into three groups: control group (n=76), study 1 group (n=78), and study 2 group (n=70). The control group was treated with tropisetron hydrochloride for 30 minutes before chemotherapy. Study 1 group was given tropisetron hydrochloride and acupuncture combination therapy 30 minutes before chemotherapy. Study 2 group was given tropisetron hydrochloride treatment 30 min before chemotherapy and acupuncture treatment 30 min after chemotherapy. Collect patients’ general information and compare the three groups of white blood cell count, G-CSF, GM-CSF levels, quality of life and KPS score, platelets, neutrophils, hemoglobin levels, TCM symptom scores, and the degree of digestive tract reaction. Results. The data of the control group and study groups 1 and 2 are comparable in gender, age, pathological type, etc. (P>0.05). Before treatment, the white blood cell counts of the three groups were not significantly different (P>0.05), significantly reduced after treatment, but the difference between the groups was not statistically significant (P>0.05). The levels of G-CSF and GM-CSF in the three groups were not substantially different before treatment (P>0.05). The levels of G-CSF and GM-CSF were considerably lowered in all three groups, although the drop in the study group was more significant (P>0.05) when compared to that in the control group. Before treatment, the quality of life and KPS score of the three groups were not statistically different (P>0.05). The three groups’ quality of life and KPS scores fell after treatment, with the study 1 group experiencing the greatest reduction, followed by the study 2 group and the control group. The levels of platelets, neutrophils, and hemoglobin in all three groups declined dramatically, with the most noticeable reduction in the control group, followed by study 2 and study 1. The difference between the three groups was statistically significant (P<0.05). The TCM symptom scores of the three groups showed an upward trend, but compared with those of the study 1 group and study 2 group, the TCM symptom scores of the control group increased significantly and the difference between the three groups was statistically significant (P<0.05). The effective rates of the control group, study group 1, and study group 2 were 42.11%, 82.05%, and 62.86%, respectively; compared with that of the control group, the treatment efficiency of study groups 1 and 2 was higher and the difference between the three groups was statistically significant (P<0.05). Conclusion. Tropisetron hydrochloride is an effective treatment for patients with lung cancer before chemotherapy, which can effectively improve the side effects of nausea and vomiting caused by chemotherapy, reduce the white blood cell count, and improve the quality of life of patients; it plays an important role in the improvement of prognosis.